Comparison of RDW PLR value with CRP and NLR values in patients with postoperative leakage and abscess after pancreatectomy (Annals of Medical Research, 2023)
Aim: New studies show red cell distribution width (RDW) to be altered by inflammatory cell wall changes in acute pancreatitis, sepsis and critical illness. We aimed to evaluate the efficacy of RDW, platelet lymphocyte ratio (PLR) and neutrophil lymphocyte ratio (NLR) values in patients who underwent pancreatectomy.Materials and Methods: Fifty patients who underwent pancreatectomy were retrospectively compared. The study group consisted of patients who were followed up with clinical or laboratory evidence of either leakage or infection, with proof of infection being culture positivity and associated fever, tachycardia, and elevated laboratory values. The control group, on the other hand, comprised of 25 patients with uneventful postoperative course. RDW, neutrophil, platelet (PLT), aspartate aminotransferase (AST), alanine transaminase (ALT), C reactive protein (CRP), PLR and NLR values of the patients were compared among and between groups at 4 different time points (1: admission, 2: postoperative first week prior to infection, 3: at the time of infection and 4: discharge). Results: Statistically significant results were obtained for ALT, CRP, neutrophil, and PLR ratios (p=0.003, p=0.002, p=0.028, p=0.032, respectively). Significant differences were also observed in RDW 2, RDW 3 and RDW 4 (p=0.034, p=0.010, p=0.031, respectively). Regarding CRP levels, significant differences were found for CRP 1 and CRP 3 levels (p=0.001, p=0.025, respectively). A significant difference was detected only for the PLR 4 value (p=0.009).Conclusion: In patients who underwent pancreatic resection and were suspected of having infection that progressed to a septic state, the levels of RDW, CRP, PLT, and PLR were observed to be correlated with infection and increased at various intervals before the culture results and evidence of infection emerged. Due to their association with the emergence of infections, these parameters have been proven to be effective and affordable tools in clinical decision-making.
Keywords: Pancreatectomy; Leak; RDW; CRP; PLR; Sepsis